Stakes too High for Women? Gendered Examination of an Education Reform in Kenya - Hang Thu Nguyen-Phung; Nahashon Nzioka Nthenya (Social Education Research, 2022)
This paper examines the relationship between women's education and their empowerment, using six waves of the nationally representative Kenya Demographic and Health Surveys (KDHS). We utilize the change in the educational system in 1985 as a source of positive exogenous shock. We particularly focus on women who were exposed to the new regime and how their exposure status affects their perceptions and practices in decision-making. The Ordinary Least Squares regression (OLS) results indicate an increase in education for women exposed to this reform, followed by a delay in their age at first birth, a reduction in female genital mutilation practices on their eldest daughters, a decrease in sexual domestic violence, and enhancement in their household decision-making. Media exposure, partners' characteristics, and wealth endowment are the possible pathways through which women's empowerment is achieved.